The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.968484
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mindfulness upbringing perception on social entrepreneurship orientation: A moderated mediation model of prosocial motivation and perceived pressure from external stakeholders

Abstract: Driven by economic and social benefits, social enterprises create new development models that combine wealth creation, social welfare provision, and environmental improvement through innovative approaches. The social entrepreneurship orientation reflects the behavioral tendency to transplant entrepreneurship orientation into the field of social value creation. It is a strategy to balance and integrate economic interests and social interests, which has a significant impact on social entrepreneurship performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 115 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…This means H4 is rejected. A study conducted in India by Shan and Tian (2022) reported similar findings, revealing that pressure from external stakeholders does not moderate the relationship between prosocial motivation and social entrepreneurship orientation that could, in turn, influence their access to finance.…”
Section: Discussionmentioning
confidence: 75%
“…This means H4 is rejected. A study conducted in India by Shan and Tian (2022) reported similar findings, revealing that pressure from external stakeholders does not moderate the relationship between prosocial motivation and social entrepreneurship orientation that could, in turn, influence their access to finance.…”
Section: Discussionmentioning
confidence: 75%
“…In the context of green development, the emergence of social entrepreneurship has had a substantial effect on shaping perceptions, driving socioeconomic implications, and influencing environmental impacts (Hübel et al, 2023;Khan et al, 2023;Oni & Fiseha, 2022;Shan & Tian, 2022;Trabskaia et al, 2023). Social entrepreneurship has the potential to effect positive societal change by means of its innovative business models.…”
Section: E Social Entrepreneurship In Green Initiativesmentioning
confidence: 99%
“…Research on social entrepreneurial motivation has focused primarily on the general antecedents of social entrepreneurial behaviour, such as empathy, altruism, moral obligation, prosocial motivation, proactive personality, compassion and intrinsic motivation (Yamini et al, 2022;Tiwari et al, 2022;Asante et al, 2020; NEJE Usman et al, 2022;Yu et al, 2021;Rambe and Ndofirepi, 2021;Kruse et al, 2021;Urban and Galawe, 2020;Douglas and Prentice, 2019;Pittz et al, 2017). Other research points to factors like workplace spirituality and creativity (Blaga, 2021;Shan and Tian, 2022;Miller et al, 2012) and even cultural influences such as uncertainty avoidance and in-group collectivism as shaping social entrepreneurial behaviour (Canestrino et al, 2020). However, the literature also suggests that possessing these motivations does not guarantee engagement in social entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%